A crosssectional descriptive study of breastfeeding behaviour and galactogogue use among privatesector patients in Cape Town South Africa - N Steyn; E Decloedt; M Zunza (South African Medical Association, 2017)
Background. Failure to exclusively breastfeed is often caused by a perception of insufficient breastmilk supply. Galactogogues are frequently prescribed in these circumstances, but this is supported by sparse scientific data with safety concerns for both mother and infant. The exact extent of galactogogue use in South Africa (SA) is not well known.Objectives. To assess breastfeeding behaviour, galactogogue use and perceived galactogogue side-effects among patients attending International Board Certified Lactation Consultant (IBCLC) private practices.Methods. We administered a self-developed, expert-reviewed questionnaire in five IBCLC private practices within the Cape Town Metropole, SA. All patients attending the practices during an 8-week period were invited to participate.Results. Data from 104 participants were included in the study. An exclusive breastfeeding rate of slightly more than 50%, associated with greater parity (p=0.029), was found. Perceived lack of breastmilk predicted galactogogue use (p=0.013). There was a high prevalence of galactogogue use (54%), with 80% of these participants using non-prescription medication. Sulpiride was the most common prescription medication used. Increased milk production was reported by 41% (n=23) of galactogogue users, while 30% (n=17) reported no effect. Most reported side-effects were minor.Conclusions. Prevalence of galactogogue use exceeded other published data. Sulpiride was most frequently prescribed, despite not being recommended during breastfeeding. A large group of participants reported poor efficacy. The effect of vaginal delivery and immediate skin-to-skin contact after delivery on milk production might be smaller than previously reported in mothers who are personally motivated to breastfeed. Healthcare practitioners should acknowledge breastfeeding mothers’ concerns regarding insufficient milk supply and emphasise correct breastfeeding technique